Features of educational work in Aulieata region before the beginning of the XX century - Байдалиев, Дархан; Дүйсенбаев, Абай; Ақжолова, Ақтоты (Pedagogy and Psychology, 2022)
The article is devoted to the history of pedagogy as an actual branch of pedagogical science. The Aulie-Ata region from the early epochs impresses with its culture, monuments of historical architecture, and is also known as a center of art and education. In this region, the development of education and science dates back to ancient times. The article comprehensively considers the main aspects of the principles of development of the educational process in the regions of Aulie-Ata. Also, religious trends in education and upbringing, at the end of the XIX th century and at the beginning of the ХХ th centuries, were justified in the Aulie-Ata region. Infrequently mentioned first scientists-enlighteners of the Aulie-Ata region, as well as the main features of their positions are described in various scientific sources. On a scientific basis, the information is analyzed that the Muslim education system, which was established before the establishment of Soviet power, in turn, went a long way of development and became the basis of the educational process.